Microsoft Windows 2000 : Illustrated complete - Carey, Patrick; Johnson, Steven M.; Salkind, Neil J. (Cambridge MA : Course Technology, 2000)
This book is about: Getting started with Windows 2000; Working with Windows Programs; Managing files using my computer; Managing folders and files using; Windows explorer...
Keywords: Microsoft Windows; Operating systems; Microsoft Windows (Computer file); Operating systems (Computers)